Comparison of Vascular Function, Cardiometabolic Parameters, Hemorheological Function, and Cardiorespiratory Fitness Between Middle-Aged Korean Women With and Without Obesity—A Pilot Study - Park, Hun-Young; Jung, Won-Sang; Kim, Sung-Woo; Jung, Kyounghwa; Lim, Kiwon (Frontiers in Physiology, 2022)
This study aimed to compare vascular function, cardiometabolic parameters, hemorheological function, and cardiorespiratory fitness in middle-aged Korean women according to obesity defined using body mass index (BMI). A total of 32 Korean women aged between 34 and 60 years (16 without obesity, mean age 46.31 ± 7.49 years and 16 with obesity, mean age 49.68 ± 6.69 years) participated in this study. Obesity was defined as BMI ≥ 25 kg/m2. The body composition, vascular function, cardiometabolic parameters, hemorheological function, and cardiorespiratory fitness of all participants were measured. Statistical differences in the dependent parameters between individuals with and without obesity were analyzed, and the correlations between BMI and the dependent variables were verified. The obese group showed significantly worse results (p < 0.05) for body composition (significantly higher weight, BMI, fat mass, and percent body fat), vascular function [significantly higher branchial ankle pulse wave velocity (baPWV) and lower flow-mediated vasodilation (FMD)], cardiometabolic parameters [significantly higher insulin and homeostatic model assessment for insulin resistance (HOMA-IR)], hemorheological function (significantly lower erythrocyte deformability and higher aggregation), and cardiorespiratory fitness [significantly lower maximal oxygen uptake (VO2max)] compared to the non-obese group. In addition, BMI showed a significant positive correlation (p < 0.05) with baPWV (r = 0.430); total cholesterol (r = 0.376), triglyceride (r = 0.411), low-density lipoprotein cholesterol (r = 0.462), and insulin (r = 0.477) levels; HOMA-IR (r = 0.443); and erythrocyte aggregation (r = 0.406), and a significant negative correlation (p < 0.05) with VO2max (r = −0.482) and FMD (r = −0.412). Our study confirmed that obesity is a major determinant for deterioration of vascular function, cardiometabolic parameters, hemorheological function, and cardiorespiratory fitness.